Epoxy modified porphyrin leveling agent and preparation method thereof

By using epoxy modified porphyrin leveling agent to adjust the deposition distribution of copper foil and improve water solubility, the problem of poor surface roughness and thickness uniformity of lithium battery copper foil is solved, significantly improving its tensile strength and elongation, and achieving efficient effect of flattening and depositing copper.

CN119875101APending Publication Date: 2025-04-25WUHAN OXIRAN SPECIALTY CHEM CO
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411978373.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium battery copper foil has poor surface roughness, poor thickness uniformity, high-temperature tensile strength and low elongation.

Method used

Epoxy modified porphyrin leveling agent is used, which is obtained by substitution of tetraaminophenyl porphyrin by ethylene oxide blocks. The deposition distribution of the copper foil is adjusted by adsorption in high current density areas to achieve the leveling effect of the plating, and improve water solubility and wetting ability through external polyether groups.

Benefits of technology

It significantly improves the surface appearance and mechanical properties of lithium battery copper foil, eliminates defects such as pinholes and lump sand on the surface of the coating, and achieves efficient flattening and depositing copper, ensuring surface roughness and thickness uniformity, and at the same time improving tensile strength and elongation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875101A_ABST
    Figure CN119875101A_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy modified porphyrin leveling agent and a preparation method thereof. The epoxy modified porphyrin leveling agent is obtained by partially or completely substituting hydrogen groups on amino groups and imino groups on tetraaminophenyl porphyrin by ethylene oxide blocks. Compared with the existing leveling agent, the epoxy modified porphyrin leveling agent provided by the invention can obviously improve the surface appearance and mechanical property of a copper foil, eliminate the defect phenomena of pinholes, hemp sand and the like on the surface of a plating layer, realize high-efficiency flat copper deposition, ensure the surface roughness and thickness uniformity, have excellent tensile strength and ductility, and can be widely applied to the field of copper plating. And the appearance stability and the performance quality of the copper foil are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plating solution used for copper electroplating, and particularly relates to an epoxy-modified porphyrin leveler and a preparation method thereof. Background Art

[0002] With the transformation of global energy structure and the improvement of environmental awareness, the new energy vehicle market continues to expand, and the demand for lithium batteries and performance requirements continue to grow. As an important raw material for lithium batteries, lithium battery copper foil has a profound impact on battery performance due to its tensile strength, elongation, density, surface roughness, thickness uniformity and appearance quality. Therefore, in the manufacturing process of lithium battery copper foil, whether it can deposit a coating that meets the above requirements is the key to its process.

[0003] At present, the acid copper plating solution system used to prepare lithium battery copper foil mainly includes basic plating solution and copper plating additives, among which the basic plating solution includes metal salts, acids, and chloride ions, and the additives mainly include three categories: brighteners, wetting agents, and leveling agents. Brighteners have the function of refining crystal particles, increasing polarization, producing high over-points to ensure high supersaturation of adsorbed atoms, or increasing the disorder of adsorbed atoms entering the lattice through their own adsorption on the surface, or hindering the diffusion of adsorbed atoms to the growth center. Wetting agents can reduce the interfacial tension between the base metal and the solution, making the additives easier to adsorb and disperse, and play a wetting and even plating effect. Most of the wetting agents are sulfur-containing organic substances, such as thioalkanes, thiosulfates, disulfides, heterocyclic thiazoles, thiazolines, thioketones, etc. Leveling agents inhibit copper deposition by adsorbing on high current density areas at the tip such as the orifice, further improving the copper ion dispersion ability, and achieving the purpose of microscopic leveling of the coating.

[0004] Traditional leveling agents usually use nitrogen-containing heterocyclic compounds or non-heterocyclic aromatic compounds. Pinholes, pitting and other surface unevenness are prone to occur on the copper foil surface, which in turn affects the copper foil's tensile strength, elongation, appearance quality and other properties, and can no longer meet the quality performance requirements of lithium battery copper foil. Therefore, it is particularly important to develop a leveling agent that can improve the surface flatness of lithium battery copper foil. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an epoxy-modified porphyrin leveler and a preparation method thereof in view of the deficiencies in the prior art. The epoxy-modified porphyrin leveler can solve the problems of poor surface roughness, poor thickness uniformity, low high-temperature tensile strength and low elongation in the existing lithium battery copper foil.

[0006] The invention provides an epoxy-modified porphyrin leveler, which is obtained by partially or completely replacing the hydrogen groups on the amino group and the imino group on tetraaminophenylporphyrin with ethylene oxide blocks.

[0007] The molecular structural formula of the epoxy-modified porphyrin leveler of the present invention is as follows:

[0008]

[0009] The position where N on the porphyrin macrocycle is replaced by epoxy is random, and a1, a2, b1, b2, c1, c2, d1, d2, e1, and e2 are integers greater than 0.

[0010] The present invention also provides a method for preparing the above-mentioned epoxy-modified porphyrin leveler, and the specific steps are as follows:

[0011] 1) Preparation of tetraaminophenylporphyrin: Under an inert atmosphere, 4-nitrobenzaldehyde, a catalyst and a solvent are first mixed uniformly, and then pyrrole is slowly added dropwise. After the addition is complete, a reflux reaction is performed, followed by cooling and separation to obtain a black precipitate. The black precipitate is purified to obtain tetranitrophenylporphyrin. The obtained tetranitrophenylporphyrin is dissolved in concentrated hydrochloric acid, and stannous chloride is added to perform a reduction reaction (reducing the nitro group to an amino group), and post-processing is performed to obtain tetraaminophenylporphyrin;

[0012] 2) Epoxy-modifying tetraaminophenylporphyrin: dissolving the tetraaminophenylporphyrin obtained in step 1) in petroleum ether (petroleum ether is used as a solvent), then adding a catalyst and mixing evenly, the reaction system is sealed and protected by an inert atmosphere, the air pressure is 0.04-0.06MPa higher than the atmospheric pressure, first heated to 130-140°C, adding 10-20wt% of the total amount of ethylene oxide (EO) for initiation, and after the pressure of the reaction system drops to 0.1MPa, the temperature is raised to the epoxy ring-opening addition polymerization reaction temperature, and the remaining ethylene oxide is continuously added. After the addition is completed, an epoxy ring-opening addition polymerization reaction is carried out, and after the reaction is completed, the reaction is neutralized with glacial acetic acid, and finally the solvent is separated to obtain an epoxy-modified porphyrin leveler.

[0013] The reaction formulas are shown in (1) and (2):

[0014]

[0015]

[0016] According to the above scheme, the catalyst in step 1) is lactic acid, and the mass ratio of the 4-nitrobenzaldehyde to the catalyst is 1:5-10.

[0017] According to the above scheme, the solvent in step 1) is nitrobenzene, and the mass ratio of the 4-nitrobenzaldehyde to the solvent is 1:30-35.

[0018] According to the above scheme, the mass ratio of 4-nitrobenzaldehyde to pyrrole in step 1) is 2-3:1.

[0019] According to the above scheme, the process conditions of the reflux reaction in step 1) are: reaction temperature is 120-130°C, and reaction time is 2-3h.

[0020] According to the above scheme, the method for purifying the black precipitate in step 1) is: first, the black precipitate is soaked in excess anhydrous ethanol at low temperature for 20-30 hours (to remove excess acid and raw materials), and then the black solid precipitate is washed with N,N-dimethylformamide (DMF) and methanol in turn after filtering, and the product tetranitrophenylporphyrin is obtained after drying.

[0021] According to the above scheme, the mass ratio of the tetranitrophenylporphyrin to concentrated hydrochloric acid (36-38wt%) in step 1) is 1:100-120.

[0022] According to the above scheme, the mass ratio of tetranitrophenylporphyrin to stannous chloride in step 1) is 1:4-5.

[0023] According to the above scheme, the process conditions of the reduction reaction in step 1) are: reaction temperature is 80-100°C, and reaction time is 1-2h.

[0024] According to the above scheme, the post-treatment method of step 1) is: the reaction solution is cooled to 0°C, then neutralized with ammonia water, filtered to obtain gray-green crystals, dried and dissolved with acetone, filtered again to obtain a dark red filtrate, and the obtained filtrate is spin-dried to obtain blue-purple crystals, which are tetraaminophenylporphyrin.

[0025] According to the above scheme, the mass ratio of tetraaminophenylporphyrin to petroleum ether in step 2) is 1:1-2.

[0026] According to the above scheme, the catalyst in step 2) is at least one of potassium methoxide, potassium hydroxide, sodium hydroxide, and sodium ethoxide, preferably potassium hydroxide, and the amount of the catalyst is 0.5-1.0‰ of the total mass of tetraaminophenylporphyrin and petroleum ether.

[0027] According to the above scheme, the molar ratio of the tetraaminophenylporphyrin in step 2) to the total amount of ethylene oxide added is 1:8-24.

[0028] According to the above scheme, the conditions for the epoxy ring-opening addition polymerization reaction in step 2) are: reacting at 140-160° C. for 0.5-1 h.

[0029] The present invention also includes a copper electroplating solution obtained based on the epoxy-modified porphyrin leveler. The copper electroplating solution includes copper sulfate, sulfuric acid, hydrochloric acid, a brightener, a wetting agent and the epoxy-modified porphyrin leveler.

[0030] According to the above scheme, the brightener is one or a mixture of 3-mercapto-1-propane sodium sulfonate, 2-dimethylamino-1,3-dithiosulfonate sodium propane, 1-butylsulfonic acid-3-methylimidazole trifluoromethane sulfonate, polydisulfide propane sodium sulfonate, and thiazoline disulfide propane sodium sulfonate, and the concentration of each component is 8-20 mg / L.

[0031] According to the above scheme, the wetting agent is one or a mixture of polyethylene glycol, polypropylene glycol, and hydroxyethyl cellulose, and the concentration of each component is 24-30 mg / L.

[0032] Preferably, the main components and concentrations of the copper electroplating solution are: copper sulfate pentahydrate 180-230 g / L, sulfuric acid 50-70 g / L, hydrochloric acid 20-40 mg / L, sodium polydisulfide propane sulfonate 16-20 mg / L, sodium 3-mercapto-1-propane sulfonate 8-10 mg / L, polyethylene glycol 6000 24-30 mg / L, hydroxyethyl cellulose 24-30 mg / L, and epoxy-modified porphyrin leveler 12-16 mg / L.

[0033] The present invention also includes a lithium battery copper foil prepared by using the copper electroplating solution.

[0034] As a porphyrin compound, tetraaminophenylporphyrin has a large π electron system that is easy to adsorb due to its special molecular structure, and has easily polarizable nitrogen atoms, so it is very easy to adsorb on the cathode surface with negative charge, especially in the high current density area, so as to slow down the electrodeposition there, and does not affect the deposition in the low current density area to achieve the leveling effect on the coating, and has excellent leveling effect. At the same time, the thermal stability and photoelectric performance of tetraaminophenylporphyrin are also more excellent than traditional leveling agents, which can promote the electron transfer process in the electroplating solution, accelerate the electroplating reaction rate, and enhance the stability and operability of the electroplating solution, but due to its poor water solubility, it will be subject to many restrictions in actual production and use. The present invention is carried out epoxy modification to tetraaminophenylporphyrin, and by controlling the process conditions, the modified product is enhanced in water solubility, the application range is widened, and the external polyether group can also play a wetting effect, reduce interfacial tension, promote bubble overflow, eliminate the generation of defects such as pinholes and pitting on the surface of lithium battery copper foil, and improve leveling and wetting ability at the same time.

[0035] The epoxy-modified porphyrin leveler provided by the present invention is used in combination with a brightener containing a sulfur heterocyclic structure and a polyether wetting agent in an acidic sulfate plating solution. Specifically, the polyether wetting agent is selectively adsorbed on the cathode to produce a strong inhibitory effect, and is oriented and arranged on the solution interface to produce adsorption, thereby improving the leveling and wetting effects; at the same time, the epoxy-modified porphyrin leveler is selectively reduced at the cathode to produce a moderate depolarization adjustment, and the brightener containing a sulfur heterocyclic structure undergoes a coordination reaction with copper ions in the cathode double layer to generate a surface complex, and a bright plating layer with a dense and flat surface and good bonding with a substrate is obtained through the comprehensive action of the additives.

[0036] The beneficial effects of the present invention are: 1. The epoxy-modified porphyrin leveler provided by the present invention has unsaturated π bonds such as -C=C-C=C- and easily polarized nitrogen atoms, and is easily adsorbed in high current density areas to adjust the deposition distribution of copper foil, thereby achieving a leveling effect. At the same time, the external polyether group can improve the water solubility and enhance its wetting ability. Compared with existing levelers, it can significantly improve the surface appearance and mechanical properties of copper foil, eliminate pinholes, hemp sand and other defects on the coating surface, and achieve efficient and smooth copper deposition. While ensuring the surface roughness and thickness uniformity, it has excellent tensile strength and elongation, effectively improving the appearance stability and performance quality of the copper foil. 2. The preparation method of the present invention has a simple process.

[0037] It is easy to industrialize and has good economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a photo of a lithium battery copper foil prepared by Example 4 of the present invention based on the epoxy-modified porphyrin leveler obtained in Example 1;

[0039] Figure 2 This is a photo of a lithium battery copper foil prepared in Example 4 based on the epoxy-modified porphyrin leveler obtained in Example 2;

[0040] Figure 3 This is a photo of a lithium battery copper foil prepared in Example 4 based on the epoxy-modified porphyrin leveler obtained in Example 3;

[0041] Figure 4 This is a photo of the lithium battery copper foil prepared in Comparative Example 1;

[0042] Figure 5 This is a photo of the lithium battery copper foil prepared in Comparative Example 2;

[0043] Figure 6 This is a photo of the lithium battery copper foil prepared in Comparative Example 3. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below using embodiments in conjunction with the accompanying drawings.

[0045] Example 1

[0046] An epoxy-modified porphyrin leveler, the preparation method of which is as follows:

[0047] 1) Preparation of tetraaminophenylporphyrin: Under N2 atmosphere, 7.78 g of

[0048] 4-nitrobenzaldehyde, 200mL nitrobenzene (240g) and 50mL lactic acid (60.3g) were heated to 125°C, and then 3.38g pyrrole was slowly added dropwise. After the addition was completed, the mixture was refluxed at 125°C for 2.5h. The solution changed from yellow to brown and then to dark black. After the reaction was completed, the mixture was cooled to room temperature, and a black precipitate was separated. 250mL of anhydrous ethanol was added to the black precipitate, and the mixture was stored in a refrigerator for 24h. The mixture was taken out and filtered. The filter cake was washed with DMF and methanol in turn, and finally dried to obtain tetranitrophenylporphyrin with a yield of about 20%.

[0049] 2) Take 1g of tetranitrophenylporphyrin, add 100mL of concentrated hydrochloric acid (36wt%, 118g), then add 4g of stannous chloride, heat to 80°C, stir and react for 1.5h, cool to 0°C and keep the temperature stable, then add 25wt% ammonia water to neutralize to pH 9-10, filter to obtain gray-green crystals, dry the crystals and dissolve them in acetone, filter to obtain a dark red filtrate, and spin-dry the filtrate to obtain 0.95g of blue-purple crystals, which is tetraaminophenylporphyrin;

[0050] 3) Preparation of epoxy-modified porphyrin leveler: 67.4 g of tetraaminophenylporphyrin (0.1 mol), 70 g of petroleum ether, and 0.137 g of KOH were added to the reactor, and the reactor was checked for air tightness. After passing the air tightness test, the reactor was replaced with N2 three times, and then the N2 was discharged and the pressure was set to 0.04-0.06 MPa slightly higher than the atmospheric pressure. After adjusting the heating device to a set temperature of 130-140 ° C, the stirring device was turned on, and 5.3 g of EO is added to the reactor for initiation. After the system pressure drops to 0.1Mpa, the reaction temperature is controlled at 140-160℃, and EO is added again until the total amount of EO added is 35.24g (0.8mol). After the EO feeding is completed, the reaction temperature is kept constant for 1 hour. When the pressure in the reactor no longer drops (at this time, EO is consumed and the pressure reaches stability), the temperature is lowered to 60-80℃, and N2 is introduced above the liquid surface in the reactor for replacement twice (to replace the possible unreacted EO to ensure safety), and the material is discharged. Finally, the product is neutralized with glacial acetic acid, the pH value is adjusted to 6-7, and then the distillation temperature is adjusted to 110-120℃ to separate the petroleum ether to obtain the product. The pressure in the reactor should not exceed the specified pressure (0.6MPa) during the entire reaction process.

[0051] Example 2

[0052] An epoxy-modified porphyrin leveler, the preparation method of which is similar to that of Example 1, except that the total amount of EO added is 1.6 mol.

[0053] Example 3

[0054] An epoxy-modified porphyrin leveler, the preparation method of which is similar to that of Example 1, except that the total amount of EO added is 2.4 mol.

[0055] Example 4

[0056] According to the epoxy-modified porphyrin leveler of Examples 1-3, three kinds of electroplating copper solutions were prepared respectively, and their main components and concentrations were: 200 g / L copper sulfate pentahydrate, 60 g / L sulfuric acid, 30 mg / L hydrochloric acid, 20 mg / L sodium polydisulfide dipropane sulfonate, 10 mg / L sodium 3-mercapto-1-propane sulfonate, 30 mg / L polyethylene glycol 6000, 30 mg / L hydroxyethyl cellulose, and 14 mg / L epoxy-modified porphyrin leveler. The electroplating copper solution was stirred by blowing air through an air pump to make it evenly mixed.

[0057] Before pre-plating, the 0.5 mm thick copper foil was pre-soaked in 0.1 mol / L dilute hydrochloric acid for 15-20 seconds, and the surface oxide layer was polished to remove. During electroplating, the copper foil was placed in a Hull cell containing the above electroplating copper solution, and the current intensity of the Hull cell was adjusted to 10 A / min, and the electroplating time was 10 min. The electroplating process was uniformly bubbling. After the electroplating was completed, the cathode plate was rinsed with pure water, and then placed in a post-treatment sealant SL-398A solution, the sealant concentration was 20%, and the soaking time was 30 seconds. Then the moisture on the copper foil was blown dry to obtain a lithium battery copper foil. According to the different sources of the epoxy-modified porphyrin leveling agent, the obtained lithium battery copper foils were marked as Examples 1-3 respectively.

[0058] Comparative Example 1

[0059] The copper electroplating solution was prepared, which was different from Example 4 only in that the epoxy-modified porphyrin leveler was replaced with an equal mass of aliphatic amine ethoxy sulfonate AESS, and the lithium battery copper foil was prepared using the same method as Example 4.

[0060] Comparative Example 2

[0061] The copper electroplating solution was prepared, which was different from Example 4 only in that the epoxy-modified porphyrin leveler was replaced with an equal mass of propane pyridinium sulfonate PPS, and the lithium battery copper foil was prepared using the same method as Example 4.

[0062] Comparative Example 3

[0063] The copper electroplating solution was prepared, which was different from Example 4 only in that the epoxy-modified porphyrin leveler was not added, and the lithium battery copper foil was prepared using the same method as Example 4.

[0064] Figure 1-3 The following are photos of lithium battery copper foils prepared in Example 4 based on the epoxy-modified porphyrin levelers of Examples 1-3, Figure 1 The sample contains a small amount of pitting and pinholes. Figure 2 and Figure 3 The surface of the sample is smooth and flat, without defects such as pinholes and pits.

[0065] Figure 4 This is a photo of the lithium battery copper foil prepared in Comparative Example 1. Figure 5 This is a photo of the lithium battery copper foil prepared in Comparative Example 2. Figure 6 This is a photo of the lithium battery copper foil prepared in Comparative Example 3. It can be seen that Figure 4 and Figure 5 There are a lot of pits on the surface, the surface is rough and the flatness is poor. Figure 6 The coating has no luster and the surface is rough. The flatness is very poor as can be seen from the thickness and warpage. The leveling effect is relatively poor. Figure 4 , 5 Worse.

[0066] With reference to the national standard GB / T 29847-2013 "Test Method for Copper Foil for Printed Circuit Boards", the lithium battery copper foil prepared in Example 4 and Comparative Examples 1-2 was tested for thickness, warpage, room temperature tensile strength, and room temperature tensile elongation. The tensile strength and tensile elongation test at high temperature is to put the copper foil into a 180°C oven and bake it for 2 hours, and then test the tensile strength and tensile elongation according to the method in GB / T29847-2013. The oxidation resistance test is to put the lithium battery copper foil into a 20°C passivating agent (sodium dichromate 200-300g / L, sulfuric acid 10-40g / L) for passivation for 7-8s, then wash it with water, blow it dry, put it in an oven, and after baking it at 140°C for 15 minutes, observe whether there is any oxidation discoloration on the surface of the copper foil. The test results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] It can be seen from Table 1 that when the epoxy-modified tetraaminophenylporphyrin prepared in Examples 1-3 of the present invention is added as a leveling additive for lithium battery copper foil, combined with a brightener, a wetting agent and suitable electroplating process conditions, compared with the leveling additives commonly used in existing lithium battery copper foils, the basic physical properties of the lithium battery copper foil can be significantly improved, including the rough surface thickness, tensile strength and elongation under normal and high temperature conditions, while meeting the flatness requirements of the lithium battery copper foil, having high tensile strength and strong antioxidant performance, achieving efficient and level copper deposition, and effectively improving the performance of the copper foil.

[0071] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

[0072] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. An epoxy-modified porphyrin leveler, characterized in that: It is obtained by partially or completely replacing the hydrogen groups on the amino and imino groups on tetraaminophenylporphyrin with ethylene oxide blocks.

2. A method for preparing the epoxy-modified porphyrin leveler according to claim 1, characterized in that: The specific steps are as follows: 1) Preparation of tetraaminophenylporphyrin: Under an inert atmosphere, 4-nitrobenzaldehyde, a catalyst and a solvent are first mixed uniformly, and then pyrrole is slowly added dropwise. After the addition is complete, a reflux reaction is performed, and then a black precipitate is obtained by cooling and separation. The black precipitate is purified to obtain tetranitrophenylporphyrin. The obtained tetranitrophenylporphyrin is dissolved in concentrated hydrochloric acid, and stannous chloride is added to perform a reduction reaction, and post-treatment is performed to obtain tetraaminophenylporphyrin; 2) Epoxy-modifying tetraaminophenylporphyrin: dissolving the tetraaminophenylporphyrin obtained in step 1) in petroleum ether, then adding a catalyst and mixing evenly, the reaction system is sealed and protected by an inert atmosphere, the air pressure is 0.04-0.06MPa higher than the atmospheric pressure, first heated to 130-140°C, adding 10-20wt% of the total amount of ethylene oxide for initiation, and after the pressure of the reaction system drops to 0.1MPa, the temperature is raised to the epoxy ring-opening addition polymerization reaction temperature, and the remaining ethylene oxide is continuously added. After the addition is completed, an epoxy ring-opening addition polymerization reaction is carried out, and after the reaction is completed, the reaction is neutralized with glacial acetic acid, and finally the solvent is separated to obtain an epoxy-modified porphyrin leveler.

3. The preparation method of the epoxy-modified porphyrin leveler according to claim 2, characterized in that, The catalyst in step 1) is lactic acid, and the mass ratio of the 4-nitrobenzaldehyde to the catalyst is 1:5-10; the solvent in step 1) is nitrobenzene, and the mass ratio of the 4-nitrobenzaldehyde to the solvent is 1:30-35; the mass ratio of the 4-nitrobenzaldehyde to pyrrole in step 1) is 2-3:1; the process conditions of the reflux reaction in step 1) are: the reaction temperature is 120-130°C, and the reaction time is 2-3h; the mass ratio of the tetranitrophenylporphyrin in step 1) to concentrated hydrochloric acid is 1:100-120; the mass ratio of the tetranitrophenylporphyrin in step 1) to stannous chloride is 1:4-5; the process conditions of the reduction reaction in step 1) are: the reaction temperature is 80-100°C, and the reaction time is 1-2h.

4. The preparation method of the epoxy-modified porphyrin leveler according to claim 2, characterized in that: Step 2) The mass ratio of tetraaminophenylporphyrin to petroleum ether is 1:1-2.

5. The preparation method of the epoxy-modified porphyrin leveler according to claim 2, characterized in that: Step 2) The catalyst is at least one of potassium methoxide, potassium hydroxide, sodium hydroxide and sodium ethoxide, and the amount of the catalyst is 0.5-1.0‰ of the total mass of tetraaminophenylporphyrin and petroleum ether.

6. The preparation method of the epoxy-modified porphyrin leveler according to claim 2, characterized in that: The molar ratio of the tetraaminophenylporphyrin to the total amount of ethylene oxide added in step 2) is 1:8-24; the conditions of the epoxy ring-opening addition polymerization reaction in step 2) are: reacting at 140-160° C. for 0.5-1 h.

7. A copper electroplating solution obtained based on the epoxy-modified porphyrin leveler according to claim 1, characterized in that: The copper electroplating solution comprises copper sulfate, sulfuric acid, hydrochloric acid, a brightener, a wetting agent and the epoxy-modified porphyrin leveler according to claim 1.

8. The copper electroplating solution according to claim 7, characterized in that: The main components and concentrations of the copper electroplating solution are: 180-230 g / L copper sulfate pentahydrate, 50-70 g / L sulfuric acid, 20-40 mg / L hydrochloric acid, 16-20 mg / L sodium polydisulfide dipropane sulfonate, 8-10 mg / L sodium 3-mercapto-1-propane sulfonate, 24-30 mg / L polyethylene glycol 6000, 24-30 mg / L hydroxyethyl cellulose, and 12-16 mg / L epoxy-modified porphyrin leveler.

9. A lithium battery copper foil prepared using the copper electroplating solution according to claim 7 or 8.

Citation Information

Cited By

  • Additive of 1-micron electrolytic copper foil and preparation method of 1-micron electrolytic copper foil

    CN121915467A

  • Additive for 1-micron electrolytic copper foil and method for producing 1-micron electrolytic copper foil

    CN121915467B